'We are not North Korea': propaganda and professionalism in the People's Republic of China. (March 2017) - Simons, Margaret; Nolan, David; Wright, Scott
This article draws on an empirical analysis of the testimonies of Chinese journalists to (re)consider the nature of professionalism in contemporary Chinese journalism. We draw on earlier work by a number of scholars to develop an analysis of the testimonies in order to trace both how professionalism is shaped by cultural, social, organizational, institutional and political influences, and how these work to shape everyday journalistic practices and outputs. We conclude that professionalization is best understood not as a shift towards an ideal version of autonomous, public service–oriented journalism, but instead as a process informed by diverse and somewhat contradictory influences, including many that are internal to China as well as some that are near universal. Not only are journalists clearly concerned to be distinguished from 'propagandists', but editors also engage in tactical practices and organizational strategies that allow a meaningful autonomy from the state. These are not only influenced by conflicting normative discourses of journalism but have also become both a necessity for establishing the legitimacy of individual journalists and news institutions and to facilitate their viability in highly competitive news markets.